Subjectivity, freedom, and human action - Miklaszewska, Justyna (Journal of Public Governance, 2014)
This paper analyzes the relationship between the concept of the individual and their ability to make free and rational choices, both individual and collective. The problem has been discussed in the works of many contemporary liberal philosophers and economists: Arrow, Buchanan, Rawls, and Sen. The latter focuses mainly on an acting person and on the concept of capabilities which stem from freedom of the individual, and create the basis for the theory of justice. These studies show that liberal political philosophy and economics can no longer be considered a value-free domain.